An Assessment of Leadership Styles towards Students Academic Performance in Government Secondary Schools of Wolaita and Dawro Zones, South Ethiopia (Global Journal of Human-Social Science, 2015)
The major purpose of this study was to assess the leadership styles practiced by principals of the secondary schools towards students academic performance of Wolaita and Dawro Zones. In order to achieve the objective of the study, descriptive survey method was employed. The study was conducted in four government secondary and preparatory schools of Wolaita Zone and three Secondary and Preparatory Schools of Dawro Zone. The schools were selected by simple random sampling techniques. Teachers were selected by systematic sampling while principals were selected by using the availability sampling. The study included 14 principals and 280 teachers. Questionnaires, observation and document analysis were used to collect data. Data were analyzed using percentages, mean and weighted mean. Based on the analysis the study portrayed that almost all principals and teachers were first degree holders, considerable number of principals were not specialized in the management fields of study and less stake holders' involvement in the decision making process were found to be the major factors. Hence, it is recommended that each schools' principals should be provided with appropriate training and development in stake holder involvement, communication with stake holders, appropriate leadership styles and team work.
Keywords: assessment; leadership; leadership styles; academic performance and secondary schools